Diet Diversification in Bombyx mori Larvae: The Impact of Dandelion on Nutritional and Bioactive Profiles for Targeted Farming Goals - Aleksandra Trajković; Danka Dragojlović; Gordana Stojanović; Ivana Zlatanović Đaić; Milenko Ristić; Marijana Ilić Milošević; Saša S. Stanković; Vladimir Žikić; Nataša Joković (Insects)
The domesticated silkworm, Bombyx mori, reared for sericulture, has gained attention as a promising, sustainable protein source. While studies have focused on pupal powders obtained through natural or artificial mulberry-based diets, this research builds on ethnoentomological knowledge of the use of dandelion as a short-term mulberry substitute, in a mixed mulberry–dandelion diet throughout larval development. Through proximate analyses, amino acid and fatty acid profiling, mineral and carbohydrate composition, as well as antioxidant activity assays, we investigated how dietary variation affects B. mori larvae. The mixed diet achieved a distinct nutritional profile, increasing total amino acids to 38.40 g/100 g compared to 32.37 g/100 g in the mulberry-only group, with differences in the content of essential amino acids like isoleucine (2.24 vs. 1.42 g/100 g) and phenylalanine (3.34 vs. 2.82 g/100 g). It also elevated linolenic acid to 74.33% of total fatty acids and introduced sorbitol (13.35 mg/g). Those two compounds were not detected in the larvae reared on a single-plant diet. HPLC-DAD analysis revealed phenolic acids, flavonoids, and riboflavin in both groups, which may serve as potential carriers of antioxidant activity. These preliminary findings demonstrate how dietary modifications can change nutritional profiles and antioxidant properties of B. mori. At the same time, they lay the foundation for further research to fully understand diet-induced effects in edible insects.